New Members of the Centrapalus Coumarin and Pauciflorin Series from Centrapalus pauciflorus - Muhammad Bello Saidu; Gordana Krstić; Petra Bombicz; Sourav De; Anita Barta; Hazhmat Ali; István Zupkó; Róbert Berkecz; Umar Shehu Gallah; Dóra Rédei; Judit Hohmann (MDPI AG, 2024)
Monoterpene and 5-methylcoumarin- or 5-methylchromone-coupled meroterpenoids occurring mainly in the Asteraceae species proved to have high potency against protozoans, worms, and various tumor cells, which make them interesting targets for searching for new bioactive compounds. The African plant Centrapalus pauciflorus was applied in traditional medicine for healing chest pain and stomach aches. Three new meroterpenoids named centrapalus coumarin N (2), pauciflorins P (3), and Q (4), and the already known cyclohoehnelia coumarin (1), were isolated from the chloroform extract of C. pauciflorus, together with centrapalus coumarin O (5), which was obtained for the first time from a natural source. The structures were established from HRESIMS, 1D (1H NMR, 13C NMR JMOD) and 2D NMR (HSQC, HMBC, 1H-1H COSY, NOESY) spectroscopies, and the absolute stereochemistry of 5 was determined by single-crystal X-ray diffraction. Compounds 1, 2, and 5 are hybrid molecules of 5-methylcoumarin-monoterpene origin. Centrapalus coumarin N is the first example of meroterpenoids, where a monoterpene is fused with a coumarin and an acetophenone unit. Pauciflorins P and Q are dimeric meroterpenoid isomers. Centrapalus coumarins N and O were tested for antiproliferative activity against human adherent breast (MCF-7, MDA-MB-231), cervical (HeLa, SiHa), and ovarian (A2780) cancer cell lines, and were additionally included to obtain data concerning cancer selectivity. Both compounds exhibited moderate (IC50 > 10 µM) but selective activity against A2780 cells.